Quantification of turbulence in cryogenic liquid using high speed flow visualization. (July 2016) - Gopalaswami, Nirupama; Laboureur, Delphine M.; Mentzer, Ray A.; Mannan, M. Sam
Abstract: A high speed flow visualization experiment was conducted to characterize the boiling induced turbulence when a cryogenic liquid is released on water. The advective transport of turbulent structures traversing through the liquid was captured and reconstructed using image processing software to obtain information on velocity components. The numerical results obtained from image processing were used to determine turbulence parameters like turbulent intensity, turbulent kinetic energy and eddy dissipation rate. An interesting aspect of the study was the formation of wavy structures called 'thermals' which were characteristic of turbulent convection. The thermals were found to act as a catalyst in increasing heat transfer and turbulence between water and cryogenic pool. The turbulent intensity was influenced by the turbulent velocity and had direct effects on the vaporization flux. Among the turbulence parameters, increase in turbulent kinetic energy resulted in faster vaporization of cryogenic liquid through enhanced mixing, whereas variations in the eddy dissipation rate had weak dependence on vaporization. Additionally, the initial height of cryogenic liquid was also found to strongly affect the vaporization mass flux. Highlights: High speed flow visualization experiment to investigate the turbulence phenomenon of cryogenic liquids released on water. The turbulence parameters have a direct influence on vaporization flux. The vaporization mass flux of liquid nitrogen directly dependent on initial cryogenic liquid height.